Economic Growth and Socioeconomic Sustainability in BRICS Countries: A Vector Error Correction Modeling Approach - Awolusi, Olawumi Dele (Journal of Economics and Behavioral Studies, 2021)
A major problem to the BRICS goal of achieving sustainable economic growth for members is the increasing level of socioeconomic inequality in the bloc. Consequently, the purpose of this study is to understand the influence of economic growth on socio-economic sustainability in the BRICS countries, using a yearly dataset from 1990 to 2019. A multivariate co-integration technique by Johansen and Juselius and Granger causality test were used to establish the relationships. Findings confirmed co-integration and short-run causal relationships. The most interesting results were the negative influence of economic growth on socio-economic inequality, tacit support for the resource curse hypothesis. The paper concluded that a common policy option was not possible and that for the block to pursue its economic prosperity goals without compromising individual countries’ needs for socioeconomic sustainability, varied policy options were inevitable. The policy implications and recommendations are straightforward: the radical legal basis for the transition from natural resource export, as well as, sweeping regulation for the sustainable usage of natural resources protection, strict penalties on violations of environment-related laws and policies to enhance, general country-wide support. In addition, there may be an urgent need to define the active role of NGOs and other independent institutions in promoting socioeconomic equality (sustainability) practices and concepts at both local and national levels, enhanced social programs; market development, Integration of existing policies and creation of societal culture. Consequently, to the best of the researcher’s knowledge, no study has investigated comprehensibly (along with multiple determinants) the sustainability of growth policy options within BRICS with an aim to proposing socioeconomic sustainability and growth policy options.